Germination of Seed in Dry Teak (Teclona grandis L.) (1) Preliminary Studies in Fruit Development and Seed Dormancy - Joshi, M. D.; Kelkar, S. P. (Indian Forester, 1971)
All the seeds in the tetralocular fruit of teak are not uniformly developed. On an average one seed is fully developed and three remain undeveloped. Out of apparently fully developed seeds, only 20 per cent show positive response to quick viability test. Out of the remaining 80% only 40% give second degree of staining and 40% do not give any staining at all with tetrazolium. The negative response to quick viability test with tetrazollum might be due to high lignification of the pericarp and endocarp before fruit drop (in the centripetal direction, advancing with the age of the fruit) which limits the gaseous exchange, particularly oxygen supply. High temperature seems to be a predisposing factor for accelerating the process of lignification. The anatomical studies of the teak fruit revealed the presence of tubular appendages, (probably of placental origin) extending right from the hilum up to the regular quadruple openings in the pericarp, through U-shaped depressions in the endocarp. These tubular appendages which remain unlignified for considerable time might have a functionary role of gaseous exchange during the process of seed development and after ripening and might be helping in water imbibition at the time of germination.